Synodality and Kerygma: Women's Involvement In Evangelization In St. Pius X Bengkayang Parish, West Borneo - Rasid, Cristin Natalia; Iskandar, Sumodiardjo; Chandra, Herwindo (Litbang STFT Widya Sasana Malang, 2025)
Women are an integral part of the Church. Their involvement has a significant influence in pastoral work. However, the role of women is often still faced with a patriarchal culture that favors men. The Church continues to struggle with the issue of gender equality and is increasingly opening up space for the role of women. This study aims to analyze the involvement of women in the pastoral work of the Church, especially in the field of kerygma or proclamation, and how their role can be strengthened in the context of synodality. The main focus of this research is to understand the attitude of the Church that is necessary for women to actively participate in pastoral work, especially in the task of proclamation. The method used was a combination of descriptive quantitative and qualitative phenomenology. The research respondents were women who are members of the WKRI (Catholic Women of the Republic of Indonesia) categorical group of St. Pius X Parish, Bengkayang, West Borneo. From the results of the research, the Church's inclusive and supportive attitude is key to increasing women's active participation. The Church needs to implement policies related to women, conduct ongoing coaching and training, change women's mindset, and provide time flexibility. The results of this study can enrich the theory of synodality and feminism in religious contexts, as well as encourage Church pastoralists to implement programs that involve women and build collaboration with external parties.